ENHANCING STUDENTS’ PRONUNCIATION AND SPEAKING SKILLS THROUGH GOOGLE TRANSLATE AND STORYTELLING - idrus, Muhammad; Nurhaedah Gailea; Rita Handayani (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This classroom action research investigates the usage of Google Translate and storytelling to improve pronunciation and speaking skills of eighth-grade EFL students at SMPN 1 Majasari. Pronunciation remains a major challenge due to students’ reliance on L1 phonology, limited access to native-like input, and fear of speaking mistakes. To address this, the study employed two CAR cycles across eight meetings, combining pronunciation practice through Google Translate’s text-to-speech (TTS) and expressive storytelling performances using narrative texts. Data collection involved pre-tests, post-tests, observation checklists, and field notes, analyzed quantitatively and qualitatively. In Cycle I, Google Translate helped students improve phoneme articulation and word stress, reflected in a rise from an average pre-test score of 5.09 to 7.34. However, students still lacked fluency and expression. In Cycle II, storytelling activities enhanced intonation, rhythm, and confidence, raising post-test scores to 16.25 and resulting in “Good” performance for most students. The findings support previous studies (Niño, 2025; Ibrahim, 2022) indicating that digital tools and interactive strategies complement each other effectively. This research confirms that combining Google Translate and storytelling addresses both segmental and suprasegmental pronunciation issues and fosters student engagement, confidence, and speaking fluency. The study recommends this integrated approach to improve pronunciation and speaking skills in EFL classrooms. Keywords: Pronunciation, Speaking Skills, Google Translate, Storytelling, Classroom Action Research.